Detection of rapid identification of microbial pathogens and emerging contaminants in water samples using cost-effective biochemical and molecular methods - Hamza Fardjave, Wadah Kadim; V.V, Novochadov; Khlaif, Abbas T. (Journal of Neonatal Surgery, 2025)
Biochemical and immunological methods are based on the analysis of various classes of organic and inorganic compounds that are defective in various hereditary diseases, primarily in hereditary metabolic diseases. Biochemical disorders, as a rule, precede the appearance of clinical symptoms of the disease and are more constant compared to them. The subject of biochemical diagnostics can be proteins, amino acids, carbohydrates, lipids, metal ions, etc., as well as their metabolites. In this case, various tissues and secretions of the body can be examined (blood, urine, saliva, sweat, cerebrospinal fluid, amniotic fluid, biopsy of muscles, skin, liver and other specialized tissues). Biochemical methods play a primary role in the diagnosis of hereditary metabolic disorders. In some cases, they allow the identification of heterozygous carriers of mutations. The role of biochemical methods of analysis is very important in conducting mass examinations of pregnant women or newborns for the purpose of earlier detection of hereditary diseases. The key role in the pathogenesis of any monogenic disease belongs to the primary biochemical defect - a protein encoded by a mutant gene. Detection and analysis of the primary biochemical defect, determination of the primary pathological metabolic chain - these are the main tasks of biochemical genetics, the solution of which is the basis for the development of pathogenetic methods for the prevention and treatment of hereditary diseases. No less important is the role of biochemical methods in the diagnosis of secondary disorders. For example, the main biochemical defect in Duchenne / Becker muscular dystrophy is a deficiency of dystrophin, a protein that connects the cytoskeleton of muscle cells with the extracellular matrix.